Rouge :
Also subtitled: Hebdomadaire d'action communiste, Quotidien communiste révolutionnaire, Hebdomadaire communiste révolutionnaire, Journal d'action communiste. - See also: Rouge. Le quotidien. Journal d'action communiste (ZF 30894). - For suppl. to no.288 see: Una voz mas (ZDK 41516).